Unveiling paths to inclusion: harnessing insights from college and career readiness curricula models to advance inclusive elements in high school college guidance counseling - Simpson, Amy M. (My University, 2025)
In the early 20th century, the United States guided high school students toward their desired career paths through educational reforms, leading to the creation of College and Career Readiness (CCR) programs. Initially, these programs were centralized, but during the Obama administration, they became decentralized, transferring CCR efforts to state control. An inclusive CCR curriculum would empower school counselors to present students with a variety of post-secondary options, facilitate differentiation to meet all students' needs, provide support, and ensure accessibility for all students nationwide, regardless of their location. The lack of inclusive programming broadens equity gaps, particularly in urban and rural areas with higher counselor-to-student ratios. Historically, vocational guidance was established in response to the societal changes of the late 19th century, evolving into a broader form of counseling that encompasses personal and psychological support in schools. Despite the continued focus on holistic student development, challenges persist in ensuring equitable access to resources and support for college and career readiness. The “Every Student Succeeds Act” (2015), which aimed to improve college attendance, has favored four-year universities while overlooking alternative career pathways, thereby worsening existing inequities. While school counselors play a vital role in promoting CCR across the states, resource allocation and counselor-to-student ratios significantly impact the effectiveness of state programs. Disparities in curricula among states further hinder equitable access, worsened by insufficient funding and inadequate evaluation methods. Additionally, school counselors often lack specialized training in CCR programs, limiting their ability to support students effectively. Several CCR models, such as Independent Educational Consultants to classroom learning environments, pose challenges in guaranteeing equitable access and awareness for all students. Sociocultural and Constructivist theories provide the frameworks for creating inclusive curricula that emphasize social interactions, cultural contexts, and personalized learning experiences. This study addresses the gap in inclusive CCR curricula to improve inclusive practices in high school counseling. Conducting a qualitative document analysis of state CCR curricula aims to identify key components of inclusivity and recommend improvements for equitable access to post-secondary opportunities. Using deductive coding will reveal the essential elements needed to support all students in their goals beyond high school.
Keywords: College and career counseling; College and career curriculum; Inclusion; Curriculum